Challenges and opportunities for nurses during COVID-19 pandemic - Pachya, Ambika Thapa; Pachya, Uttam; Thapa, Namuna; Tandukar, Rojina; Shrestha, Jyotsna Singh; Thapa, Jeevan; Neupane, Bandana; Subedi, Madhusudan (Journal of Karnali Academy of Health Sciences, 2020)
Background: Pandemic of COVID-19 coincided with the year of Nurses and Midwives 2020. In war against invisible that has been ongoing during this pandemic, nurses play crucial role. As of June 2020, more than 600 nurses have lost their lives due to COVID-19.  Thus, there is need to review challenges that pandemic has posed as well as the avenues of opportunities that it has opened for nurses.Method: Review of existing literature on nurses, their challenges and opportunities during COVID-19 was done using electronic database. Freely accessible literatures in English language that clearly mentioned on challenges and opportunities of nurses during COVID-19 were included in the study.Result: One of thechallenges that nurses face during COVID-19 is workforce shortage. With increasing number of people infected with COVID-19, it outstretches the existing nursing health workforce, and disproportionately in the low and middle incomes countries. They are at risk of infection and have high job demand. The incidents of suicide among nurses are representation of physical distress and psychological trauma. Role of nurses in patients care during COVID-19 can be under-rated and stigmatized. Internationally trained nurses and minorities nurses are at increased risk of discrimination.Conclusion: Being the pertinent stakeholders in patient care, nurses’ faces different challenges as well as some opportunities. COVID-19 has opened avenues for advocacy of nursing profession to get acknowledged for their dedication, perseverance, high morale and contribution during the pandemic management.